The Team Games Tournament Media Box Instrument Learning Model Can Improve Learning Outcomes On Traditional Musical Instrument Classification Materials At SMP Plus Taruna Andalan Pangkalan Kerinci - Happy Siregar (LANGGAM: International Journal of Social Science Education, Art and Culture, 2023)
The aim of this research is to determine whether the implementation of the Team Games Tournament Learning Model with box instrument media can enhance the learning outcomes of eighth-grade students in class VIII-B at SMP Plus Taruna Andalan Pangkalan Kerinci on the topic of traditional musical instrument classification. This research is a Classroom Action Research (CAR) by Kurt Lewin, which consists of four stages to be followed: planning, acting, observing, and reflecting. Data collection was carried out over 2 cycles using both quantitative and qualitative data analysis techniques. From the test results conducted, starting from the pre-cycle, Cycle I, to Cycle II, there was an improvement in the average scores of students' learning outcomes. The initial average score in the pre-cycle was around 61.68. However, in Cycle I, students' learning outcomes reached an average of approximately 74.68, indicating an improvement of 13 points from the pre-cycle. A more significant improvement was observed in Cycle II, where the average learning outcomes increased to 93.37. This indicates that the Team Games Tournament Learning Model with Box Instrument media is highly effective in enhancing understanding and mastery of the material. Students were able to achieve much better learning outcomes at the end of Cycle II, approximately 31 points higher than the pre-cycle score.